Complexidade organizacional e governança corporativa nas empresas listadas na BM&FBOVESPA - Assunção, Renata Rouquayrol (2014)
The organizational complexity is seen as starting point for the separation of property and control activities, while corporate governance, which promotes the alignment of interests between the principal and the agent, might be understood as a means to enhance business control devices. In this context, the general objective of the present study is to investigate the relation between organizational/operational complexity and corporate governance in companies listed on the BM&FBovespa, by the light of the Contingency Theory Precepts, in which contingency factors might influence the organizational characteristics related to structure and to business strategies (DONALDSON, 2007). In this research, it is considered that organizational complexity refers to the complexity of structure and of formal aspects necessary to the insertion of a company into the market. The complexity of operations is related to the complex set of resources and the valid process towards the development of activities. It is important to remember that this research justifies itself in view of the few studies putting the two themes together which can be found in national literature as well as the intention to make the studies become a starting point for the analysis of business structure and the eventual necessity to implant and improve more efficient control. It consists of a descriptive research, of quantitative nature, which puts together a sample of 162 companies listed on the BM&FBovespa. For data analysis the following statistical tests have been used: Factor Analysis, Multiple Linear Regression, Correspondence Analysis, and Correlation Analysis. For measuring complexity, age, size, diversification and internationalization were the contingency variables adopted as a set; and in order to assess corporate governance, a check list made up of 16 items based on the studies of Silveira (2004), Silva and Leal (2005) and Lameira and Ness Jr. (2011) and on recommendations proposed by the Comissão de Valores Mobiliários - CVM (2002) and by the Instituto Brasileiro de Governança Corporativa - IBGC (2009) was used. Based on Factor Analysis, it was possible to identify that organizational complexity is explained by size and diversification variables while operational complexity is explained by means of size, diversification and internationalization variables. In the Multiple Linear Analysis, it was detected that the two dimensions of complexity, corporate governance is influenced by diversification, internationalization and age variables, while the latter is an inverted relation. By means of Correspondence Analysis and Correlation Analysis, it has been concluded that, no matter what dimension is being assessed, complexity relates positively and significantly to corporate governance, that is, the most complex companies listed on the BM&FBovespa display the highest levels of corporate governance, which comes as a confirmation of the research hypothesis. Such results contribute to the acquisition of knowledge on these themes when contingency theory presuppositions get confirmed and with the revelation of the existence of a field in which it is necessary for administrators to manage organizational/operational complexity in order to perceive and adhere to more and better control devices by means of the adoption of good practices of corporate governance..